IMPLEMENTATION OF THE ‘’HOPE FAMILY PROGRAM’’ POLICY AT PURABAYA DICTRICT, SUKABUMI, WEST JAVA - IJANG RUSWANDI; ERRY SUNARYA; DARMO H SUWIRYO (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
Poverty is one of the problems currently being faced by the Indonesian state. In 2007 the government implemented a conditional cash transfer program known as the Family Hope Program (PKH). One of PKH's goals is to improve the standard of living of beneficiary families. The problem that will be answered in this thesis is how to implement the Family Hope Program (PKH) in Purabaya District, Sukabumi Regency. This type of research is a field research research (field research). This research is a descriptive qualitative research. Sources of data in this study are primary data and secondary data. Where the data collection uses interview techniques, observation and documentation. To analyze the data, the authors used a triangulation descriptive analysis of the data collected by the researcher. Based on the results of research in the field, the implementation of PKH is measured through indicators of Communication, Resources, Disposition and Bureaucratic Structures in Purabaya District. This can be seen from the uneven distribution of aid recipients from the poor in Purabaya District and the limited quota of beneficiaries from the Ministry of Social Affairs.